Marriage, celibacy, and heresy in ancient Christianity The Jovinianist Controversy. - Hunter, David G..; Jovinianus (Oxford Oxford university press, 2007)
Study of the 'heretic' Jovinian and the Jovinianist controversy.The author examines early Christian views on marriage and celibacy in the first three centuries and the development of an anti-heretical tradition. He provides a thorough analysis of the responses of Jovinian's main opponents, including Pope Siricius, Ambrose, Jerome, Pelagius, and Augustine. In the course of his discussion Hunter sheds new light on the origins of Christian asceticism, the rise of clerical celibacy, the development of Marian doctrine, and the formation of 'orthodoxy' and 'heresy' in early Christianity.
Keywords: Jovinianus, -- active 385-400.; Celibacy -- Christianity -- History of doctrines -- Early church, ca. 30-600; Marriage -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600; 254*5 -- Priesterlijk celibaat; 265.5 -- Huwelijk; 273 "00/04" -- Schisma's. Ketterijen--?"00/04"